The effect of copper additives on hybrid Zr-based chemical conversion coating morphology and chemical compositions - Ankita Mohanty; Xiaoyang Liu; Cheng-Chu Chung; Donald Vonk; Kim Kisslinger; Xiao Tong; Andrew Kiss; Gary Halada; Stanislas Petrash; Kate Foster; Yu-chen Karen Chen-Wiegart (Applied Surface Science Advances)
In the realm of corrosion protection, Zr-based conversion coatings offer an environmentally friendly, chromate-free alternative to conventional coating. This study uses advanced X-ray, electron microscopy and electrochemical testing techniques to better understand the impact of varying Cu²⁺ ion concentrations on the characteristics of Zr-based coatings on Fe substrates. Our findings demonstrate that within the tested conditions, higher Cu²⁺ additive concentrations at 40 ppm enhance surface characteristics, increasing stability towards anti-corrosion capability, particularly under NaCl treatment. Conversely, at a lower Cu²⁺ concentration of 20 ppm, coatings exhibited more significant dissolution of Cu clusters and increased vulnerability to chloride-induced degradation. X-ray photoelectron spectroscopy and synchrotron X-ray fluorescence (XRF) and X-ray absorption near edge structure (XANES) spectroscopy analyses revealed Cu²⁺ formation in Cu20, while Cu40 retained its metallic state (Cu⁰) with a slower reaction rate. Cu20 offers some protection but lacks durability, whereas in Cu40, lower Icorr, and enhance corrosion resistance, making it ideal for protective coatings in salt-water environments. This study underscores the importance of balancing Cu²⁺ ions concentration in the coating solution to optimize performance, highlighting the role of Cu in enhancing both surface properties and long-term stability.